Timesharing properties : concept, management and legalities / Rusnani Abd. Rahman - Abd. Rahman, Rusnani (Faculty of Architecture, Planning and Surveying, 1991)
Timesharing is relatively newly practiced concept in property ownership and is practically applied especially to resort properties- It originated in Europe during 1960's and made its debut in Malaysia in early 1980"s. It is widely practiced worldwide but however, in the Malaysian scene, the industry is still at an infant stage. Nevertheless, it is fastly gaining popularity an an alternative form of property ownership. The concept of timesharing enables the use of a property by a number of owners who purchase only the specific time they use. However, today, there appears to be a changing trend in timeshare ownership and property due to the growth of the industry. Therefore, the objective of this study is aimed to obtain clearer understanding on timesharing as a new concept of real estate ownership, how it is managed and maintained and the legal aspects relating to such ownership to both purchaser and owner.